CASUAL INDONESIAN MONOFTONGIZATION IN TALK SHOWS - Fawzi, Ary; Goncalves, Agostinho dos Santos (Jurusan Sastra Indonesia, 2023)
Monophthongization is a simplification of diphthongs in language activities. This study aims to describe monophtongization, distribution, and monophtongization patterns as the impact of dialects in Indonesian. This study uses a qualitative descriptive design. The data source for this research is the utterances in talkshows that use non-formal Indonesian. The results of this study indicate that (a) monophthongization occurs in /ai/, /au/, and /ia/ diphthongs; (b) monophthongization can occur in diphthongs at the beginning, middle, and end of words; and (c) the dialect of each speaker influences monophthongization events in the non-formal variety of Indonesian.